FAKTOR-FAKTOR YANG MEMENGARUHI PENGUNGKAPAN HAL AUDIT UTAMA (HAU) (Studi Empiris pada Perusahaan Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Hadziqan Syah Elfajri; Herry Laksito (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the effect of auditor characteristics and corporate governance on the disclosure of key audit matters (KAM) in Indonesia. The independent variables include public accounting firm size, auditor gender, audit committee meeting frequency, audit committee financial expertise, and independent commissioners. In addition, the study incorporates control variables consisting of firm complexity, profitability, and leverage.The sample comprises financial sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2022 to 2024. A total of 286 observations were selected using a purposive sampling method based on specific criteria. Data analysis was conducted using panel data multiple linear regression with the assistance of SPSS version 30.The results show that auditor gender and the frequency of audit committee meetings have a positive and significant effect on KAM disclosure. Meanwhile, public accounting firm size, audit committee financial expertise, and independent commissioners do not have a significant effect. These findings indicate that individual auditor characteristics and effective internal oversight activities play an important role in promoting transparency in key audit matter disclosures.